Mengembangkan Kepemimpinan dan Etika: Meningkatkan Tanggung Jawab dan Kompetensi Pengurus KOPMA USD - Januari Ayu Fridayani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to develop leadership attitudes and ethics as well as a sense of responsibility among responsive and competent KOPMA USD administrators. The main problem faced is the lack of understanding and application of good leadership principles among the administrators. The methods used in this study include training, workshops, and intensive mentoring. The results show a significant improvement in the understanding and application of leadership ethics and responsibility among the KOPMA USD administrators. The administrators have become more responsive and competent in carrying out their duties, which is reflected in the increased performance of the organization and the satisfaction of KOPMA USD members. This study concludes that the leadership and ethics development program is effective in improving the quality of KOPMA USD administrators.